Respectus Philologicus, 2010 Nr. 17 (22) - Bankauskaitė, Gabija (Respectus Philologicus, 2010)
CONTENTSI. PROBLEMS AND SOLUTIONSJurga Cibulskienė (Lithuania). Are Ideologies Reflected in Metaphors?...11Lara N. Sinelnikova (Russia). The Addresser as an Alter Ego of the Addressee...26II. FACTS AND REFLECTIONSOleg N. Grinbaum (Russia). Chapter 3 in Pushkin’s Novel Eugene Onegin: Rhythm and Sense in Tatiana Larina’s Letter ... 43Jadvyga Krūminienė (Lithuania). Oscar Milosz as Translator: Playing Games with Memory... 55Magdalena Ożarska (Poland). 19th-Century Lake District as a Land of Tourists, Homemakers and Writers: a Selection of Writings by Dorothy Wordsworth, William Wordsworth and Harriet Martineau... 67Inga Bartkuvienė (Lithuania). Definitions of Nationality in the Theory of Homi K. Bhabha...79Mindaugas Grigaitis (Lithuania). Deconstruction of Jaques Derrida: Theoretical Postulates and Possibilities of Practice... 94Janusz Detka (Poland). Eastern Episode in Polish Poetry of 1955–1957... 106Kristina Bačiulienė (Lithuania). The Worldview of Marcelijus Martinaitis’ Collection of Poems K. B. Suspect... 120Yelena A. Nakhimova (Russia). Metaphorical Projection and Conceptual Integration in Political Communication... 130Anna Biyumena (Belarus). Verbs of Period and Existence in Political Discourse... 139Anna V. Vladimirova, Tatyana G. Skrebtsova (Russia). Discourse Strategies in Women and Men’s Glossies as a Reflection of Gender-Specific Behaviour... 148Joanna Bryła (Poland). Phraseological Units in Fashion Advertisements...159Michael Louis Bakalinsky (Ukraine). New Theory and Methodology of Social Dialect Studies: US Underworld Social Dialect as a Case in Point... 170Tatiana V. Poplavskaia, Tatiana I. Svistun (Belarus). The Interrelation between Types and Functions Abbreviations Perform in the Internet-Discourse... 186Vilhelmina Vitkauskienė (Lithuania). Review of Research Methods on Language E-Learning Interactions ...195Bernd Gliwa (Latvia), Daiva Šeškauskaitė (Lithuania). What Does Dievmedis (God’s Tree) Have in Common with God(s)?...205III. OPINIONOlga Jagintseva (Estonia). The Ethnolinguistic and Etymological Aspects of the Noun Glyok ‘an Earthenware Jug’ ... 219IV. OUR TRANSLATIONSPatrick Seriot (Switzerland). Oxymoran or Misundersanding. Anna Wierzbicka’s Universal Relativism of Natural Semantic Metalanguage. Part II. Translated by Vilhelmina Vitkauskienė... 227V. SCIENTIFIC LIFE CHRONICLEBooks reviewsSaulius Lapinskas (Lithuania). MELNIKIENĖ, Danguolė, 2009. Dvikalbiai žodynai Lietuvoje: megastruktūros, makrostruktūros ir mikrostrutūros ypatumai... 233Eleonora Lassan (Lithuania). ЛАРИНА, Татьяна, 2009. Категория вежливости и стиль коммуникации. Сопоставление английских и русских лингвокультурных традиций... 237Galina Michailova (Lithuania). ЧЕРНЫХ, В. А., 2008. Летопись жизни и творчества Анны Ахматовой. 1889–1966... 241Barbarа Greszczuk (Poland). LUCIŃSKI, Kazimierz, 2009. Языковые заимствования и ментальность... 247Announce ... 249VI. REQUIREMENTS FOR PUBLICATION... 250VII. OUR AUTHORS... 258
Keywords: none